Spatio-temporal analysis of soil loss and sediment export using GIS and the InVEST-SDR model: application in the Rio Pardo Basin, Brazil - Nicolete, Donizeti Aparecido Pastori [UNESP]; Piroli, Edson Luís [UNESP] (Elsevier, 2025)
Identifying areas with high erosion rates and sediment source is essential for effective natural resource management and land use and land cover (LULC) planning in river basins. This study applied the Revised Universal Soil Loss Equation (RUSLE), integrated with the Sediment Delivery Ratio (SDR) module of the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, to estimate water erosion and sediment transport rates in the Rio Pardo Basin (RPB), located in southeastern Brazil. This basin has experienced changes in LULC in recent years, which have affected soil loss and sediment delivery. From 2003 to 2023, results showed an increase in the classes of highest erosion intensity (slight/moderate, moderate, moderate/high, high, very high and severe), with a 17.4 % reduction in the slight class, evidencing the intensification of surface erosion processes in the RPB, mainly driven by LULC changes. The average SDR values were 0.033 and 0.034 for the years analyzed, while the average sediment export rate for 2023 was 0.22 Mg ha−1 yr−1, higher than the average in 2003, which was 0.16 Mg ha−1 yr−1. To refine the spatial analysis, the RPB was divided into four sub-basins, with the sub-basin called Baixo Pardo presenting the highest erosion rates, SDR, and sediment export. Hotspot analysis further confirmed critical erosion areas in Baixo Pardo and the headwaters of other sub-basins. This study provides a useful tool and methodological approach for decision-makers to implement conservation practices, supporting water security in the RPB and similar areas.